Efektifitas dan keamanan dari terapi kombinasi methotrexate dan secukinumab pada Psoriasis vulgaris berat: tinjauan sistematis - Ovienanda Kristi Purbasari; Ni Putu Wina Widyastuti; Carolina Senak (Intisari Sains Medis, 2021)
Introduction: Psoriasis is a chronic inflammatory disease of the skin that requires comprehensive treatment. Combination therapy can be a good option in optimizing psoriasis treatment outcomes. However, the effectiveness and safety of combination therapy are still not fully understood. This study reviewed the literature examining the effectiveness and safety of the combination treatment of secukinumab and methotrexate in patients with severe Psoriasis vulgaris.Methods: A literature search was performed on PubMed and Google Scholar databases, with several inclusion criteria. The research method used is a case report and controlled trial, with the critical appraisal method using the JBI Critical Appraisal.Result: There were 6 pieces of literature that met the inclusion criteria. All literature describes in detail the clinical condition, course of the disease, management and side effects of treatment, but supporting examinations are not specifically described. In general, all literature shows a clinical improvement in severe psoriasis patients who are given combination treatment, and some literature also explains systemic side effects and residual plaque. The combination of biological agents with conventional systemic treatment has been proposed to optimize the results of psoriasis treatment. One study reported lightweight gastrointestinal disorders related to the use of a combination of secukinumab and methotrexate administration along with biological agents that could prevent or reduce the development of anti-drug antibodies and increase response levels to treatment. Advanced research is still needed in assessing this specific mechanism for this combination therapyConclusion: Combination therapy of secukinumab and methotrexate is effective in treating psoriasis skin manifestations without significant side effects. This drug combination is useful in overcoming the limitations of monotherapy drugs, such as decreasing effectiveness due to prolonged use. Pendahuluan: Psoriasis merupakan penyakit inflamasi kronik pada kulit yang membutuhkan penanganan yang baik. Terapi kombinasi  dapat menjadi pilihan yang baik dalam mengoptimalkan luaran pengobatan psoriasis. Namun, efektifitas dan keamanan terapi kombinasi masih belum dipahami sepenuhnya dan masih harus di pertimbangkan. Studi ini menilai beberapa literatur yang menguji efektifitas dan keamanan dari pengobatan kombinasi secukinumab dan methotrexate pada pasien dengan Psoriasis vulgaris berat. Metode: Pencarian literatur dilakukan pada database PubMed dan Google Scholar, dengan beberapa kriteria inklusi. Metode penelitian yang digunakan adalah case report dan controlled trial, dengan metode critical appraisal menggunakan JBI Critical Appraisal.Hasil: Didapatkan sebanyak 6 literatur yang memenuhi kriteria inklusi. Semua literatur menjelaskan secara detail terkait kondisi klinis, perjalanan penyakit, tatalaksana dan efek samping pengobatan, namun pemeriksaaan penunjang tidak dijelaskan secara spesifik. Secara umum, semua literatur menunjukan adanya perbaikan klinis pada pasien psoriasis berat yang diberikan pengobatan kombinasi, beberapa literatur juga menjelaskan efek samping sistemik dan plak residu. Terapi kombinasi agen biologis dengan pengobatan sistemik konvensional telah diusulkan untuk mengoptimalkan hasil pengobatan psoriasis. Satu studi melaporkan adanya gangguan gastrointestinal ringan terkait penggunaan kombinasi secukinumab dan methotrexate. Pemberian methotrexate bersamaan dengan agen biologis dapat mencegah atau mengurangi pengembangan antibodi anti-drug dan meningkatkan tingkat respon terhadap pengobatan. Penelitian lanjutan tetap diperlukan dalam menilai mekanisme spesifik terapi kombinasi ini.Kesimpulan: Terapi kombinasi secukinumab dan methotrexate efektif dalam mengobati manifestasi kulit psoriasis tanpa adanya efek samping bermakna. Kombinasi obat ini berguna dalam mengatasi keterbatasan obat monoterapi, seperti efektifitas yang menurun akibat penggunaan yang berkepanjangan.